Konseling Kelompok Ringkas Berfokus Solusi untuk Menurunkan Prokrastinasi Akademik Siswa SMP - Wardana, Andika Yuda; Rahman, Diniy Hidayatur; Multisari, Widya (Buletin Konseling Inovatif, 2025)
This study examines the effect of the solution focused brief group counseling approach on academic procrastination. This quantitative research using quasi-experimental research design. The research design used was a pretest-posttest with a control group design. The research population is all public junior high school 6 Malang eighth-grade students in the 2021/2022 academic year. The research sample was obtained through a purposive sampling of 8 students and divided into experimental and control groups. The research instrument used is the Academic Procrastination Scale. Data analysis was used to test the differences in academic procrastination before and after being given short, solution-focused counseling, namely the Mann-Whitney Test. The results of the data analysis show that the significance value is 0.02 less than 0.05, meaning that the research hypothesis is accepted. So short group counseling focused on solutions significantly reduces academic procrastination in eighth-grade students. The results of the research can be used as an alternative to help solve student problems in counseling services, especially related to reducing academic procrastination.